The Investment Policy of Deposit Guarantee Funds under Conditions of Limited Domestic Securities Markets - Žilinskas, Raimundas; Gaižauskas, Lionius (Ekonomika, 2015)
Deposit guarantee (insurance) schemes accumulate funds on the basis of guarantee (insurance) contributions. Funds are invested into particular financial instruments in order to increase them. These funds have to be used to pay pay-outs to depositors in the case of the failure of insured members. Therefore, investments must be safe, liquid, and properly diversified. This is especially important to carry out properly for deposit guarantee (insurance) schemes of countries whose domestic securities market is limited. This paper presents an analysis on investment structure of deposit guarantee (insurance) schemes of European countries under conditions of limited domestic securities markets, identifying weak points, and providing conclusions on their improvement. Based on the experience of the Lithuanian Deposit Guarantee Scheme, the structure of investments is examined, pointing to the principal problems and weaknesses of investments under conditions of a limited domestic securities market. The key factors for the investment policy are derived as a result of this analysis.
Keywords: deposit insurance; deposit guarantee; investment